Incorporation of ionic rare earth elements as a form of microbial environmental remediation - Rassy, Wadih Y.; Ripper, Doris; Pomare, Eliana; Winkler, Sebastian; Koppensteiner, Anita; Spadiut, Oliver; Schild, Dominik (Frontiers in Environmental Science, 2023)
Modern society is heavily dependent on critical raw materials, such as rare earth elements (REEs), for use in electronic devices. The increasing demand for these materials has led to the need for environmentally friendly methods of processing non-recycled materials from e-waste and wastewater, as well as waste streams from cleaning and manufacturing facilities. Modern society’s dependence on such materials is growing by the day, and with it, the need for environmentally friendly processing of non-recycled materials from e-waste and wastewater in the form of “end-of-life” products, as well as waste streams from cleaning and manufacturing facilities, also increases. As these are problematic indications for modern isolation methods in the industry, these sources may be more suitable for new techniques as they have low concentration and high throughput for bioaccumulation. Chemical methods using nanomaterials are already being tested for their possibilities but still depend on acids and harsh chemicals. Microorganisms, on the other hand, can adsorb/absorb REEs in a more ecological way. Previous studies could already show that it is possible to accumulate REEs in the precipitates of bacterial cultures spiked with REEs to a value of over 50%. However, the question arose whether rare earths were spun into the pellets by centrifugation, adsorbed, or really incorporated in the cells. Therefore, we established a new easy-to-use experimental design in which the microorganisms were spiked with an REE standard and washed to minimize the falsification of measurements by peripheral binding of ions before being analyzed for REE contents by ICP-OES. The bioaccumulation of rare earths in microorganisms was monitored, yielding an uptake rate of up to 53.12% of the overall present ionic REE concentration. In this manuscript, we present the different concentration measurements that were taken during the process, before and after washing of the cells, to create a full picture of the localization, binding, incorporation, and occurrence of the ions of interest. The setup also showed a correlation between the introduction method of rare earths and the uptake of certain elements that might be correlated with the differentiation between light and heavy rare earth elements, while Y and Sc often seem to represent outliers.